Variable High-Frequency Deep Brain Stimulation of the Subthalamic Nucleus for Speech Disorders in Parkinson's Disease: A Case Report - Zhang, Chencheng; Pan, Yixin; Zhou, Haiyan; Xie, Qing; Sun, Bomin; Niu, Chuanxin M.; Li, Dianyou (Frontiers in Neurology, 2019)
Background and Importance: It is known that subthalamic nucleus deep brain stimulation (STN-DBS) at a fixed high frequency (> 100 Hz) improves the primary motor symptoms of Parkinson disease (PD), but this stimulation does not improve or may even exacerbate the later-occurring axial symptoms and signs in PD (e.g., problems with gait or speech). Recent evidence suggests that STN-DBS at a fixed lower frequency (< 100 Hz) can improve speech and gait, but may worsen the tremor in PD. Clinical Presentation: The case involved a female patient who developed severe speech problems after 16 years high-frequency STN-DBS for PD. The tremor and dysarthria symptoms were both effectively treated by applying variable-frequency stimulation (VFS) containing only a combination of high frequencies. Conclusion: VFS containing different higher frequencies improved both the tremor and axial signs including speech problems in our patient. This case report suggests that VFS may be of clinical utility in the management of advanced PD, but this should be further verified in large well-controlled studies.